Impact of institutional and regulatory quality on FDI inflow: Case of a developing Indian economy - Leena A. Kaushal (Cogent Economics & Finance, 2021)
The study examines the impact of regulatory & institutional quality (IQ) on FDI inflows, focusing on select factors to explain evolving FDI patterns in India over 2006-2019. India, one of the top 5 FDI attracting nations in the Asian region, is taking various measures to improve IQ and encourages FDI. The reforms facilitating the Ease of starting business and reduction in EPU significantly and positively impacts FDI; however, the measures easing trade across border and resolving insolvency has a positive but insignificant impact of FDI. In addition, deteriorating Labor Freedom significantly inhibits FDI. The results demonstrate that improvement in IQ positively influences FDI; however, the IQ impact is insignificant in some cases due to the weak institutional structure. The study suggests that IQ factors tend to be pivotal in attracting FDI inflows, but India is yet to arrive.
Keywords: C1; F2; O1; 330; doing business; Foreign Direct Investment; India; institutional quality